Pengaruh Pengguna Kendaraan Listrik Terhadap Kualitas Udara Di Kota Jakarta - Hidayat, Amanda Farliany (Jurnal Ilmiah Wahana Pendidikan, 2025)
Air pollution in Jakarta has become a serious problem that impacts public health and the environment. One of the main sources of air pollution is exhaust emissions from motor vehicles. Electric vehicles, as an alternative to environmentally friendly vehicles, are expected to be a solution to overcome this problem. The main objective of this article is to raise public awareness about the potential of electric vehicles in improving air quality in Jakarta City. Air pollution in Jakarta has become a serious problem that negatively impacts public health and the environment. This article explains how electric vehicles can help reduce exhaust emissions and improve air quality. to encourage the public to consider using electric vehicles as a more environmentally friendly alternative to gasoline or diesel motor vehicles. This article explains the various advantages of using electric vehicles, such as cheaper operating costs and lower exhaust emissions. This study aims to analyze the effect of the use of electric vehicles on air quality in the city of Jakarta. Data on motor vehicle exhaust emissions and air quality data in Jakarta were collected and analyzed. The results show that the use of electric vehicles can significantly reduce motor vehicle exhaust emissions, especially NOx and PM2.5 exhaust emissions. This reduction in exhaust emissions can improve air quality in Jakarta, especially in areas with high levels of air pollution.